Moral Reasoning Memoderasi Pengaruh Ethical Sensitivity Pada Kualitas Internal Audit di PT. Bank BRI Kantor Cabang se-Provinsi Bali - Wedhasari, Ida Ayu Pradnyani; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2018)
Internal audit or internal examination is an independent appraisal function within an organization to test and evaluate the organization's activities undertaken. The purpose of this research is to analyze the moral reasoning to moderate the influence of ethical sensitivity on the quality of internal audit at PT. Bank BRI Branch Offices throughout Bali Province. This research was conducted in all offices of PT. Bank BRI Branch Office of Bali Province as many as twelve offices located in the Region of Bali in 2017 by making auditors as many as 50 people as samples through saturated sample method. The data were collected by distributing questionnaires as many as 50 respondents were tested through regression analysis moderation technique. Based on the analysis, ethical sensitivity variable has a positive effect on internal audit quality at PT. Bank BRI Branch Offices throughout Bali Province. Moral reasoning strengthens or moderates the positive influence of ethical sensitivity on the quality of internal audit at PT. Bank BRI Branch Offices throughout Bali Province. Keywords: ethical sensitivity,moral reasoning, quality of internal audit